2016
DOI: 10.7860/jcdr/2016/15082.8158
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructive Surgery Camp for Leprosy Deformities in a Tertiary Hospital: An Example of Service Delivery at Low Costs

Abstract: Reconstructive surgery in a camp setup is a low cost alternative of correcting leprosy related deformity. It also provides valuable practical experience in reconstructive surgery to surgical trainees. Tertiary hospital based camps for conducting large-scale surgeries may be a cost effective alternative to reduce waiting lists in public health sectors. Long-term studies monitoring patients operated in a camp setting would be worthwhile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Treatment of leprosy patients is also always accompanied by a self-care mechanism taught by the officer to the patient, in order to prevent the disease from worsening [21]. There is also a mechanism of rehabilitation through reconstruction, physiotherapy and the provision of aids (prosthesis) for people with disabilities level 1 or 2 [22]. DM program is managed in conjunction with other non-infectious diseases program, so there is no specificity of the DM program.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of leprosy patients is also always accompanied by a self-care mechanism taught by the officer to the patient, in order to prevent the disease from worsening [21]. There is also a mechanism of rehabilitation through reconstruction, physiotherapy and the provision of aids (prosthesis) for people with disabilities level 1 or 2 [22]. DM program is managed in conjunction with other non-infectious diseases program, so there is no specificity of the DM program.…”
Section: Discussionmentioning
confidence: 99%
“…Plantar ulcer was the commonest deformity (51.5%), while lagopthalmos (9.2%) was the least common deformity in the patient group. Also, 30.7% claw hand deformities and 6.9% ulnar nerve abscesses were found [20]. Most of the cited articles showed that hands, feet and eyes are the 3 main body parts affected by leprosy.…”
Section: Discussionmentioning
confidence: 99%
“…Shadullapur(20), and Fulchori(7). Finally, the sample consisted of 92 affected people from two divisions irrespective of age, gender, and deformity.Semi-structured questionnaire was used at the field for data collection which was pretested in Khulna.…”
mentioning
confidence: 99%
“…36 Notably, the introduction of the reconstructive surgery camp for leprosy in Gujarat, India increased reconstructive surgery for leprosy in other parts of India. 36 Reconstructive surgery is an important part of recovery from leprosy and there is great potential for reconstructive surgery to decrease disabilities caused by leprosyassociated nerve damage. 40 All in all, more study on plastic surgery is needed to establish a standardized method of surgical treatment to reduce disabilities and deformities caused by leprosy, thus improving patients' function and reducing stigma.…”
Section: Leprosymentioning
confidence: 99%
“…3). 36 Leprosy often causes a permanent disability, with 3 million people currently living with a leprosy-associated deformity (Fig. 6).…”
Section: Leprosymentioning
confidence: 99%